FERROSKUTTERUDITE (Fe, Co) As3: A NEW MINERAL SPECIES FROM THE DOLOMITE-CALCITE VEINS OF THE NORIL'SK ORE FIELD - Spiridonov E.M.; Gritsenko Yu.D.; Kulikova I.M. (My University, 2007)
Chalcogenides-sulfides, sulfoarsenides, arsenides, sulfoantimonides, and other compounds of Fe, Co, and Ni are characterized by a wide range of isomorphic substitution in the Fe–Co–Ni series. In some cases, these are continuous series of solid solutions: disulfides (pyrite–vaesite–cattierite), diarsenides (safflorite CoAs3–rammelsbergite NiAs2–lollingite FeAs2, and others ), and others. With the discovery of a new mineral, ferroskutterudite, this series was supplemented by triarsenides: skutteruditeCoAs3–nickelskutterudite NiAs3–ferroskutterudite (Fe, Co)As3. Previously, only the skutterudite–nickelskutterudite series was known.